2013
DOI: 10.7120/09627286.22.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of housing and husbandry practices on adrenocortical activity in captive Canada lynx (Lynx canadensis)

Abstract: In recent years, there has been an increasing focus on the study and assessment of animal welfare in captive settings, such as zoological gardens and aquaria. Canada lynx (Lynx canadensis) are a relatively common species in zoos, yet are known to exhibit frequent reproductive problems in captive environments. We provide an exploratory analysis of housing and husbandry factors that are associated with patterns of adrenocortical activity in lynx. Adrenocortical activity was assessed using the non-invasive techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 17 publications
4
27
1
Order By: Relevance
“…Besides husbandry conditions, veterinary procedures are also correlated with high fGM levels in different carnivore species (Malmkvist and Hansen, 2001;Rothschild et al, 2008;Young et al, 2004), but wherein especially the chemical immobilization represents a potential stressor for captive animals (Teixeira et al, 2007). In contrast to other studies demonstrating that translocations and acclimatisation to new enclosures caused strong stress responses in felid species (Carlstead et al, 1993a;Fanson and Wielebnowski, 2013;Wells et al, 2004), in our study distinct elevated fGM concentrations following translocation were only measurably in a single male (Fig. 6).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Besides husbandry conditions, veterinary procedures are also correlated with high fGM levels in different carnivore species (Malmkvist and Hansen, 2001;Rothschild et al, 2008;Young et al, 2004), but wherein especially the chemical immobilization represents a potential stressor for captive animals (Teixeira et al, 2007). In contrast to other studies demonstrating that translocations and acclimatisation to new enclosures caused strong stress responses in felid species (Carlstead et al, 1993a;Fanson and Wielebnowski, 2013;Wells et al, 2004), in our study distinct elevated fGM concentrations following translocation were only measurably in a single male (Fig. 6).…”
Section: Discussioncontrasting
confidence: 83%
“…This could be due on the fact that some of the stress events were not recognised by the keepers, potentially depending on the keepers' anthropocentric perception of the environment (Fanson and Wielebnowski, 2013). In addition the samples were not collected on a regular basis.…”
Section: Discussionmentioning
confidence: 99%
“…GC are one of the major components of the stress response (Sapolsky, 1992) and GC monitoring has been documented in previous research as a useful tool for managing animals in professional care. Fanson and Wielebnowski (2013) found that size of the enclosure was one of the main factors that correlated with GC secretion in Canadian lynx. In this study, one individual had lower GC concentrations when moved from a small enclosure to a significantly larger one.…”
mentioning
confidence: 99%
“…Effects of season on GC concentrations has been observed in zoo giant pandas, in which an individual in one study had higher GC concentrations in the winter and spring than in the summer season (Owen, Czekala, Swaisgood, Steinman, & Lindburg, 2005). Both studies used GC collection techniques that were non-invasive, one through fecals (Fanson & Wielebnowski, 2013) and the other through urine (Owen et al, 2005). These methods are valuable techniques and potentially more accurate by not having increased GC secretion caused by captureinduced stress (Millspaugh & Washburn, 2004;Millspaugh et al, 2001).…”
mentioning
confidence: 99%
“…Recommended minimum enclosure size per Lynx canadensis is 4 by 2 by 2.5 m (l by w by h) and floor area should be increased by 50% for each additional cat (Mellen 1997). Individuals should have access to at least 75% of the vertical space (Mellen 1997) along with several hiding locations (Fanson and Wielebnowski 2013). Clawing activity should be stimulated by providing rotting logs in the enclosure (Mellen 1997).…”
Section: Husbandrymentioning
confidence: 99%